Sandy beach macrofaunal communities on the western coast of Portugal – Is there a steady structure under similar exposed conditions? - Gonçalves, Sílvia C. (2012)
The structure of macrofaunal communities at two similar exposed sandy beaches on the western coast of Portugal was monitored for approximately 18 months by sampling all the beach area, from the shoreline to the base of the dunes. The beaches’ physical environment, as well as community density and composition, seasonal variations and the potential relationships between biological data and environmental parameters were studied. The two beaches had similar exposure to wave action, but differed in terms of sediment grain size, extent of the intertidal area, sediment moisture content and, especially, in the potential food availability in the form of allochthonous debris. Differences were observed with regard to the communities’ structure, namely regarding composition and relative contribution of the dominant species. Seasonality, especially temperature variations, and the interaction between seasons and the beach zones (supralittoral vs. intertidal) also had a strong influence on communities: controlling dominant species’ density and the horizontal distribution of the dominant species, and promoting a differential utilization of the beach by several resident macrofaunal animals. The present study allows the identification of key species in exposed sandy beaches of western Portugal and demonstrates that a steady community structure does not persist in the similarly exposed conditions observed, which may be mainly a response to distinct detritus subsidies, combined with differences in sediment grain size, sediment moisture content and extent of the intertidal area.